Mentalization‐based treatment in groups for adolescents with borderline personality disorder: a randomized controlled trial. (8th November 2019) - Beck, Emma; Bo, Sune; Jørgensen, Mie Sedoc; Gondan, Matthias; Poulsen, Stig; Storebø, Ole Jakob; Fjellerad Andersen, Christian; Folmo, Espen; Sharp, Carla; Pedersen, Jesper; Simonsen, Erik
Abstract : Background: Borderline personality disorder (BPD) typically onsets in adolescence and predicts later functional disability in adulthood. Highly structured evidence‐based psychotherapeutic programs, including mentalization‐based treatment (MBT), are first choice treatment. The efficacy of MBT for BPD has mainly been tested with adults, and no RCT has examined the effectiveness of MBT in groups (MBT‐G) for adolescent BPD. Method: A total of 112 adolescents (111 females) with BPD (106) or BPD symptoms ≥4 DSM‐5 criteria (5) referred to child and adolescent psychiatric outpatient clinics were randomized to a 1‐year MBT‐G, consisting of three introductory, psychoeducative sessions, 37 weekly group sessions, five individual case formulation sessions, and six group sessions for caregivers, or treatment as usual (TAU) with at least 12 monthly individual sessions. The primary outcome was the score on the borderline personality features scale for children (BPFS‐C); secondary outcomes included self‐harm, depression, externalizing and internalizing symptoms (all self‐report), caregiver reports, social functioning, and borderline symptoms rated by blinded clinicians. Outcome assessments were made at baseline, after 10, 20, and 30 weeks, and at end of treatment (EOT). The ClinicalTrials.gov identifier is NCT02068326. Results: At EOT, the primary outcome was 71.3 ( SD = 15.0) in the MBT‐G group and 71.3 ( SD = 15.2) in the TAU group (adjusted mean difference 0.4 BPFS‐C units in favor of MBT‐G, 95% confidence interval −6.3 to 7.1, p = .91). No significant group differences were found in the secondary outcomes. 29% in both groups remitted. 29% of the MBT group completed less than half of the sessions compared with 7% of the control group. Conclusions: There is no indication for superiority of either therapy method. The low remission rate points to the importance of continued research into early intervention. Specifically, retention problems need to be addressed.